Leveraging Reddit in academia - Katherine A. LaFlamme (Discover Education)
Abstract This study investigates how integrating Reddit into academic environments can enhance authentic learning experiences and strengthen information literacy skills. As a crowdsourced platform with diverse communities, Reddit provides access to a wide range of perspectives, hard-to-reach populations, and both qualitative and quantitative insights. While Reddit holds potential as a research tool, this article focuses on its application in supporting information literacy and authentic learning assignments. It examines the benefits and challenges of using Reddit in academic settings, highlighting practical applications such as project-based learning (PBL) and renewable assignments that cultivate critical thinking and collaborative learning. By incorporating Reddit into the classroom, educators can engage students in evaluating information critically, encourage collaboration, and promote deeper understanding through real-world applications, thereby positioning Reddit as a transformative tool for academic learning.